The Educational Values on Nuzulul Qur’an - Ghazali Awaluddin; Achmad Abubakar; Hasyim Haddade (At-Ta'dib, 2021)
This research is a library research, examining books and journals of theories of educational values related to the events of nuzulul Qur’an. This study aims to analyze how educational values can be learned from the events of nuzulul Qur'an. There are many events that have educational values on this earth, that educational values can be interpreted from various perspectives according to the perspective of each individual. In this discussion, the researcher explores one of the important events in Islam about the events of the revelation of the Qur’an and the educational values that are tucked in it. Starting from the phenomenon of limited access to education and blind imitation of ancestral customs, the Qur'an is coming to bring the values of wisdom, namely the stages in establishing laws from rule to rule, from one condition to another, and from one character to another character. The viewpoint of this research method presented by descriptive qualitative data, this method describe, explain and interpret what the object is. The data collection according to some theories on the educational values and nuzulul qur’ans event. Based on the findings, there are three educational values emerge from nuzulul Qur’ans event: the education of faith, the gradualness of education, the renewal of education